(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
A study related to multidimensional poverty is presented as a deprivation of the necessary resources to enjoy an adequate standard of living, in La Manga sector of the Humocaro Bajo community, Morán municipality, Lara state. It is part of the line of research Sustainability, equity and participation of the Desarrollo Humano program of the Decanato Experimental de Humanidades y Artes of the Universidad Centroccidental Lisandro Alvarado. Its objective is to show the reflections that served as the basis for selecting the methodological theoretical elements that supported the study carried out in the community. For this, different bibliographic and documentary sources focused on the central statements of the subject were analyzed, trying to establish an appropriate conceptual relationship around the notions of human development, human rights, public policies and unregulated urban settlements through a process aimed at understanding the levels of multidimensional poverty as deprivation of human rights. The conclusions highlight the importance of this new approach and the lack of updating in the traditional way of measuring poverty in the Venezuelan case.